2020
DOI: 10.1021/acs.iecr.0c00539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Number and Molecular Structure of Olefin on HDO Activity and Hydrogenation Pathway

Abstract: The hydrogenation of C7–C9 olefins, which leads to severe loss of octane number in the hydrodesulfurization process of gasoline, was investigated. The reactivity of olefins hydrogenation was affected by the branch group, CC bond position, and the distance between them. The steric hindrance caused by the branch group was decreased with the increase of the carbon number. However, the effect of the CC bond position on olefins hydrogenation increased with the increase of carbon number in olefins. Meanwhile, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The surface of the modified PVDF membrane was full of CHPEI copolymers, and the molecular structure of demulsifier determines the demulsification mechanism. When the emulsion was contacted with CHPEI, droplets change and consist of three stages: aggregation, breakup, and consolidation 45 . The hyperbranched branched chain of CHPEI provided rich active sites and aggregated droplets through bridging affect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface of the modified PVDF membrane was full of CHPEI copolymers, and the molecular structure of demulsifier determines the demulsification mechanism. When the emulsion was contacted with CHPEI, droplets change and consist of three stages: aggregation, breakup, and consolidation 45 . The hyperbranched branched chain of CHPEI provided rich active sites and aggregated droplets through bridging affect.…”
Section: Resultsmentioning
confidence: 99%
“…When the emulsion was contacted with CHPEI, droplets change and consist of three stages: aggregation, breakup, and consolidation. 45 The hyperbranched branched chain of CHPEI provided rich active sites and aggregated droplets through bridging affect. At this point, the hydrophilic CHPEI on the membrane surface penetrated to the emulsion interface and ruptures and causes the interface deformation and the rearrangement of the interface material under the increased of the surface tension of the emulsion.…”
Section: Verification Of the Demulsification Mechanismmentioning
confidence: 99%
“…According to previous studies, the structures of olefins were able to affect the reactivity of olefin hydrogenation. Dong et al investigated the relationship between the olefin structure and their hydrogenation activity using different FCC gasoline distillation fractions. They found that branched groups, internal CC bonds, and the short distance between the branched alkyl groups and the CC bond were the major factors to reduce olefin hydrogenation activity.…”
Section: Discussionmentioning
confidence: 99%
“…In respect of bifunctional catalysts herein, despite the addition of molecular sieves altered MoS 2 morphology to some extent, another reason is that the changes of acidity result in the increase of branched hydrocarbons and less olefins to be hydrogenated. Isomerization of n-olefin, to form iso-olefins with steric hindrance around the CC bond, can reduce the absorption of olefins at the HYDO active sites on CoMoS active phases . In this way, the active sites on CoMoS phases are more fully used to remove sulfur compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation